Diskursus Keperawanan: Kekerasan terhadap Seksualitas Perempuan - Damanhuri Damanhuri (Center of Gender Studies and Child of State Islamic Institute of Metro, 2020)
Virginity becomes a complicated discourse for women. It is a holiness and glory in religion and ethic, nevertheless hiding discriminated contruction for the owner. It is more grinding, when myth and medic contribute creating power-knowledge to confirm sexuality violence for this context be undisputed answer and looking at virginity as self-identity of women which must be disciplined, controlled and normalisized along time. This article attempts to describe existing concept of virginity in the mythic, medical, and Islamic discourse by using social-critics perspective as an analysis. The result shows virginity, in the mythical discourse, emerging double-ethic standard which difference between male and female. While medical discourse trys to create ‘virginity detection’ for women as control and supervising form. Interpretation, and then, of religious doctrine legitimates by which misogynic understanding tend to weakness women existing. And the end of all, virginity discourse emerges sexuality violence for women.